Imbalance of the productive structure and its effect on fluctuating government spending (Iraq case study) - Huzayran, Fahad Mghemish; Al waely, Khudhair Abbas Hussein; Mohammed Al zubaidi, Mohammed Naji (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to try to explain the reality of the imbalance of the productive structure in Iraq during the study period by providing an analysis of the indicators of the imbalance of the production structure represented by the imbalance of the structure of the agricultural, industrial, service, mining and quarrying sectors while tracking the impact of these imbalances on fluctuating government spending. As the research problem lies in the fact that the Iraqi economy has long suffered from an imbalance in its production structure and an unequal relationship between the constituent elements according to the proportions and levels determined by the economic theory. This resulted in weak growth of the sectoral contribution to the gross domestic product and the continuing rentier economy and its dependence on oil exports, which was negatively reflected on the fluctuation of government spending. The research reached several conclusions, the most important of which is the presence of a clear imbalance in the production structure of the Iraqi economy during the study period. In the first phase of the study, that is, during the nineties period, there was a great dependence on the agricultural sector because of economic sanctions on Iraq, which led to the scaling of government spending, but after 2003 it was the adoption The gross domestic product on the oil sector has increased significantly, which has led to an abundance of government revenues and reflected an increase in government spending and a clear neglect of the rest of the production sectors. The research reached several recommendations, the most important of which is the need to get rid of the rentier nature of the Iraqi economy by supporting the productive sector in the agriculture, industry and services sector by following a set of financial, monetary and commercial policies, as well as supporting the private sector and giving way to it to take its role in supporting the economy.